Back Cover: EPR Studies of V‐ATPase with Spin‐Labeled Inhibitors DCC and Archazolid: Interaction Dynamics with Proton Translocating Subunit c (ChemMedChem 4/2016). (February 2016) - Gölz, Jan Philipp; Bockelmann, Svenja; Mayer, Kerstin; Steinhoff, Heinz‐Jürgen; Wieczorek, Helmut; Huss, Markus; Klare, Johann P.; Menche, Dirk
Abstract : The back cover pictures shows the use of spin‐labeled derivatives of vacuolar‐type ATPase (V‐ATPase) inhibitors archazolid and N, N′ ‐dicyclohexylcarbodiimide (DCC) to gain insight into the binding dynamics and stoichiometry, as well as the structure, of the central functional subunit c of V‐ATPase by electron paramagnetic resonance (EPR) spectroscopy and double electron—electron resonance (DEER) measurements. V‐ATPases are hetero‐multimeric ion pumps present in the membranes of organelles of eukaryotic organisms. Their involvement in many human diseases, notably their role in the development, invasion, and progression of cancer cells makes their detailed structural analysis and molecular inhibitor interactions very important research objectives. More information can be found in the Full Paper by Markus Huss, Johann P. Klare, Dirk Menche et al. onpage 420 in Issue 4, 2016 (DOI:10.1002/cmdc.201500500 ).